2006
DOI: 10.1112/s0024609306018765
|View full text |Cite
|
Sign up to set email alerts
|

Property (T) for C*-Algebras

Abstract: A C *-algebra A is said to have the FS-property if the set of all self-adjoint elements in A has a dense subset of elements with finite spectrum. We shall show that this property is not stable under taking the minimal C *-tensor products even in case of separable nuclear C *-algebras. §1. Introduction A C *-algebra A is said to have the FS-property if the set of all self-adjoint elements in A (= A sa) has a dense subset of elements with finite spectrum. In [3], Brown and Pedersen provided the non-commutative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…Let us first recall Bekka's notion of property (T ) in [3]. Note that Bekka's definition comes from the original definition of property (T ) for groups (see e.g.…”
Section: Definitions and Basic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us first recall Bekka's notion of property (T ) in [3]. Note that Bekka's definition comes from the original definition of property (T ) for groups (see e.g.…”
Section: Definitions and Basic Propertiesmentioning
confidence: 99%
“…Bekka introduced in [3] the interesting notion of property (T ) for a pair consisting of a unital C * -algebra and a unital C * -subalgebra. He showed that a countable discrete group G has property (T ) if and only if its full (or equivalently reduced) group C * -algebra has property (T ).…”
Section: Introductionmentioning
confidence: 99%
“…Kazhdan's revolutionary concept of property T has recently been translated into C * -language in [1]. One of the questions raised by Bekka's paper is whether or not one can generalize to the C * -context the classical fact that a discrete group which is both amenable and has property T must be finite (cf.…”
Section: Introductionmentioning
confidence: 98%
“…E-mail address: nbrown@math.psu.edu. 1 Partially supported by DMS-0244807. The irritating C-summand cannot be avoided; if B is any C * -algebra with property T and C is any algebra without tracial states then B ⊕ C also has property T. Hence any finite-dimensional C * -algebra plus a Cuntz algebra (for example) will have property T and be nuclear. On the other hand, the theorem above does imply that if A is nuclear, has property T and has a faithful trace then it must be finite-dimensional-this is an honest generalization of the discrete group case since reduced group C * -algebras always have a faithful trace.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation